Galvanically Replaced Au/Ag Nanostructures as a SERS‐Active Substrate with Progressive Interior Hotspots - Young Sung Shin; Soo Hyun Lee; Iris Baffour Ansah; ChaeWon Mun; Jun‐Yeong Yang; Seunghun Lee; Dong‐Ho Kim; Sung‐Gyu Park (Advanced Sensor Research, 2023)
Abstract Interior hotspots in surface‐enhanced Raman spectroscopy (SERS) platforms have attracted intensive attention because they enable facile methodologies and exhibit excellent sensing behavior. Molecules surrounded by plasmonic materials exhibit dual functions as field‐confined regions and analytes, and their domain consistency eventually triggers the amplification of SERS signals. In this study, to conveniently realize interior hotspots, hollow regions such as voids and interstitials are strategically introduced via a galvanic reaction (GR) as a result of the difference in reduction potential between Au and Ag. The imbalanced stoichiometric ratio and diffusion fluxes induce the Kirkendall effect in conjunction with the GR between Au and Ag. SERS platforms with narrow and densified interior hotspots are optimized by controlling the reaction time. The activation of interior hotspots is confirmed using the finite‐difference time‐domain method, which indicates a theoretical enhancement factor of 1.07 × 107 based on a fourth‐power approximation. The spontaneous GR reaction enables sensing operation with high reproducibility (relative standard deviation of <10%). The proposed bimetallic platforms are used to trace methylene blue and rhodamine 6G dyes until their concentrations reach 50 nm. Therefore, the GR methodology for interior hotspot engineering demonstrates the potential for enabling the fabrication of SERS platforms with practical applications.